2023
DOI: 10.3390/s23020756
|View full text |Cite
|
Sign up to set email alerts
|

SSA-VMD for UWB Radar Sensor Vital Sign Extraction

Abstract: The combination of advanced radar sensor technology and smart grid has broad prospects. It is meaningful to monitor the respiration and heartbeat of grid employees under resting state through radar sensors to ensure that they are in a healthy working state. Ultra-wideband (UWB) radar sensor is suitable for this application because of its strong penetration ability, high range resolution and low average power consumption. However, due to weak heartbeat amplitude and measurement noise, the accurate measurement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Furthermore, Huang et al demonstrated the nanometer-precision manipulation on phase segregation of polyelemental nanomaterials. 153 The layer growth mechanism at the interface of heterostructures induced by the small lattice mismatch facilitated the unit-cell-level interface engineering, leading to the synthesis of several phase-segregated segments with a unit-cell thickness in one single particle.…”
Section: Surface/interface Engineeringmentioning
confidence: 99%
“…Furthermore, Huang et al demonstrated the nanometer-precision manipulation on phase segregation of polyelemental nanomaterials. 153 The layer growth mechanism at the interface of heterostructures induced by the small lattice mismatch facilitated the unit-cell-level interface engineering, leading to the synthesis of several phase-segregated segments with a unit-cell thickness in one single particle.…”
Section: Surface/interface Engineeringmentioning
confidence: 99%
“…Ultra-wideband (UWB) and NB antennas are increasingly being used for vital sign detection (VSD) due to their ability to operate at low power and their ability to provide accurate and reliable measurements. UWB antennas are capable of transmitting and receiving short pulses of electromagnetic waves that can penetrate through obstacles and reflect off the human body to provide highly precise measurements of vital signs such as heart rate and respiration rate [ 2 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Radar transmits electromagnetic waves and can detect chest movements through breathing and heartbeats. Analysis of the changing distances between the chest cavity and the antenna of the radar receiver represents the frequency of respiration and heartbeat [18]. Such noncontact vital signs monitoring technologies are noninvasive and inconspicuous and can alleviate patients' discomfort while enhancing convenience [8,19].…”
Section: Introductionmentioning
confidence: 99%